Overcoming academic challenges in Malaysia: Social and digital media support for Chinese undergraduates - Jiang, Meilian; Ahmad, Abdul Latiff; Aziz, Jamaluddin (Journal of International Students, 2026)
Many studies have focused on the academic adaptation of Chinese international students studying in Western countries. However, the academic adaptation of these students in Malaysia has received little attention. This paper aims to analyze the challenges faced by Chinese undergraduates in Malaysia and propose key strategies from the perspective of social and digital media support. The research employed qualitative methodologies, comprising eight focus group discussions with 40 Chinese undergraduates from four public and four private Malaysian universities, as well as interviews with six international officials from these institutions. The study revealed that Chinese undergraduates encountered a range of academic challenges, including language barriers, diverse pedagogical approaches, and issues with academic collaboration. These findings have implications for Chinese undergraduates in developing effective strategies to address academic challenges, as well as for higher education institutions and university administrators in Malaysia to increase academic support and services for international students.